Morphological features of the venous bed of the heart of the Baikal seal - Tarasevich Vyacheslav (EDP Sciences, 2021)
The article describes the features of venous blood outflow from the heart in the Baikal seal. The objects for the study were corrosion preparations of 11 hearts of the Baikal seal aged from 1 month to 10 years. In our research we used the methods of preparation, filling of vessels with the use of "Kudo" mounting foam, photographing and sketching the branching of vessels. It was established that in the Baikal seal, the outflow of venous blood occurs through the prominent coronary sinus and the large, intermediate, oblique vein of the left atrium, the middle and right heart veins that flow into it. In 18.2% of hearts, a coronary valve was found at the border of the great heart vein and the coronary sinus. The great heart vein begins above the apices of the heart and is formed from the fusing of the 6-11 collateral veins of the wall of the right ventricle, the venous pericardial plexus, and 9-16 branches on the side of the left ventricle. The most variable is the intermediate (marginal) branch, which in most cases has only one branch, however, in 18.2% of cases there are two ones or in 9.1% of cases, there are intermediate branches with a common trunk. The middle vein of the heart is located in the sub-sinus sulcus and anastomoses with the branch of the great vein of the heart, in 9.1% of cases, the valve of the coronary sinus was found at the border with the coronary sinus. The right veins of the heart have 5-6 branches, among which the marginal ones are the most prominent. 27.3% of Baikal seals have a venous sinus formed from the fusion of the middle and right coronary veins, as well as a duct connecting the large cardiac vein with this sinus.